Functionalization of Ruthenium(II)(η6‐p‐cymene)(3‐hydroxy‐2‐pyridone) Complexes with (Thio)Morpholine: Synthesis and Bioanalytical Studies. Issue 6 (5th April 2017) - Hanif, Muhammad; Meier, Samuel M.; Adhireksan, Zenita; Henke, Helena; Martic, Sanela; Movassaghi, Sanam; Labib, Mahmoud; Kandioller, Wolfgang; Jamieson, Stephen M. F.; Hejl, Michaela; Jakupec, Michael A.; Kraatz, Heinz‐Bernhard; et al.
Abstract: Hydroxypyr(id)ones constitute an emerging platform for the design of drug molecules, owing to their favorable biocompatibility and toxicity profiles. Herein, [Ru II (η 6 ‐ p ‐cymene)] complexes with 3‐hydroxy‐2‐pyridinone functionalized with morpholine and thiomorpholine, as a means often used in medicinal chemistry to alter the physicochemical properties of drug compounds, are reported. The compounds underwent hydrolysis of the Ru−Cl bond and the aqua species were stable for up to 48 h in aqueous solution, as observed by 1 H NMR spectroscopy and ESI‐MS. The compounds formed adducts with amino acids and proteins through cleavage of the pyridinone ligand. Binding experiments to the nucleosome core particle by means of X‐ray crystallography revealed similar reactivity and exclusive binding to histidine moieties of the histone proteins. Preliminary cyclin‐dependent kinase 2 (CDK2)/cyclin A kinase inhibitory studies revealed promising activity similar to that of structurally related organometallic compounds. Abstract : Designer drugs : The Ru II (η 6 ‐ p ‐cymene) complexes of 3‐hydroxy‐2‐pyridinone‐functionalized with morpholine and thiomorpholine display low cytotoxic activity (see figure). This is associated with ligand‐exchange reactions that result in cleavage of the pyridinone moiety from the ruthenium center.